Plant growth and seed quality of bean seeds under soil flooding - Pedó, Tiago; Martinazzo, Emanuela Garbin; Aisenberg, Geison Rodrigo; Aumonde, Tiago Zanata; Villela, Francisco Amaral; Antunes, Irajá Ferreira (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">The growth of plant species can be affected by flooding. The study aimed to comparatively evaluate the growth and expression of seed vigor of common bean genotypes subjected to soil flooding. For each genotypes IPR Tuiuiú and Carioca, treatments consisted of combining soil flooding for 12 hours or kept at field capacity, and plant sample collection times. Plant samples were collected at every 20 day intervals, being determined dry mass, leaf area and seed vigor. The plants of genotype IPR Tuiuiú showed higher growth and similar expression of seed vigor under soil field capacity. In plants of genotype Carioca, soil flooding did not affect growth and expression of seed vigor. The flooding negatively interferes on growth and vigor expression of bean seed, with intensity dependent on the genotype. The ratio between area and leaf mass is reduced in plants subjected to flooding. Plants of Carioca genotype subjected to flooding present greater growth and expression of seed vigor comparatively of the IPR Tuiuiú.